Genome-wide association analysis to identify QTL for carcass traits in Hanwoo (Korean native cattle) - HONG, MIN-WOOK; CHOI, SO-YOUNG; SINGH, NARESH KUMAR; KIM, HUN; YANG, SONG-YI; KWAK, KYEONGROK; KIM, JONG-BOK; LEE, SUNG-JIN (The Indian Journal of Animal Sciences, 2019)
A genome-wide association study (GWAS) was performed to investigate the genetic markers associated with carcass traits of Hanwoo (Bos taurus coreanae) steer in the Gangwon region of Korea. Hanwoo steer (139) from the Gangwon region were genotyped with Bovine SNP50K BeadChip, and 35,769 SNPs were analyzed for five specific carcass traits after applying several filters. A total of seven quantitative trait loci were detected, of which four, one, and 2 SNPs were detected on various B. taurus autosomal chromosomes (BTA) by the respective model. The four significant SNPs associated with backfat thickness were ARS-BFGL-NGS–41475 on BTA 5, ARS-BFGLNGS- 36359 on BTA 19, ARS-BFGL-NGS-56813 on BTA 22, and Hapmap25048-BTA-138242 on BTA 25. Among the detected SNPs, one and two SNPs were associated with marbling score (ARS-BFGL-NGS-110066 on BTA 23) and meat colour (BTB-01920239 on BTA 15 and ARS-BFGL-NGS-24934 on BTA 18). In this GWAS, we identified three positional candidate genes for carcass traits, backfat thickness (Fibulin-2, FBLN2; Sorting nexin 29, SNX29) and meat colour (WW domain containing oxidoreductase, WWOX). Our results suggest that the candidate SNP markers do affect the genomic selection of associated carcass traits for Hanwoo in the Gangwon region.